Peran Kepolisian dalam Pencegahan Illegal Fishing terhadap Nelayan yang Menggunakan Alat Penangkapan Ikan Pukat Hela dan Pukat Tarik Perspektif Siyasah Dusturiyah - Roni Mulyanto; John Kenedi; Miti Yarmunida (CV. Doki Course and Training, 2025)
This study aims to examine the role of the police in preventing illegal fishing against fishermen using trawl and pull fishing gear in Bengkulu from the perspective of siyasah dusturiyah. This type of research is field research with a qualitative approach, which aims to obtain descriptive data through interviews and direct observation at the Directorate of Water and Air Police of the Bengkulu Regional Police. The results of the study indicate that efforts to prevent illegal fishing by the Ditpolairud Polda Bengkulu have been carried out through various approaches, including legal socialization, sea patrols, and investigations and inquiries into perpetrators of violations. However, the optimization of the role of the police is considered not optimal, especially in the preventive-structural aspect. This is due to the lack of strong synergy and coordination between law enforcement officers and local governments in creating policies that touch on the root of the problem, such as the economic inequality of local fishermen. As for the siyasah dusturiyah study on the prohibition of the use of trawl and pull fishing gear by the Police because this act is a crime that violates norms, both in terms of religious norms, law, and the environment. To assess or measure an act as a crime depends on the values ​​and outlook on life found in society regarding what is good and beneficial for society up to the level of harm of the act.